SURVIVE DI ERA PANDEMI DENGAN PEMANFAATAN TEKNOLOGI MICROGREEN SAYUR ORGANIK - Erna Haryanti; Dwie Retna Suryaningsih; Koesriwulandari Koesriwulandari; Adi Wuryanto; Chrisanta Michelle FM (Yayasan Education and Social Center, 2021)
This community service is carried out in Dukuh Kupang Village, Dukuh Pakis District, Surabaya City. The purpose of this activity is to motivate people to change their behavior in order to respond to the conditions of the Covid 19 pandemic with activities that have economic value. In detail, the objectives of this Community Service are: a) Help solve economic problems b) Provide knowledge through counseling and assistance activities about business opportunities for organic vegetables using microgreen techniques. c) Develop a spirit of independence through entrepreneurial activities, so that they can improve their economic capacity. The implementation of this community service applies the community participation method, namely the Participatory Rapid Rural Appraissal( PRRA) and Rapid and Rural Apraissal (RRA) methods, which provide opportunities for the target together with the implementing team to synergize in planning, organizing, implementing and controlling the implementation of this activity. Materials transferred through counseling and training include: Entrepreneurship, marketing techniques, institutional management as well as training and assistance in the implementation of Microgreen cultivation techniques. The targets of this Community Service activity are: 1) The application of vegetable cultivation technology with Microgreen technology 2) This cultivation activity can be developed as a sustainable entrepreneurial activity